The ethics of research - Callieri, Bruno (Medicina e Morale, 2024)
The ethical problem of research proposes itself beyond any theoretical radicalisation that wants to conclude in a self-sufficient positive science or in a denial of any scientific reality. While man's need to place himself ethically (with a transcendence of himself and the reality that surrounds him) remains alive, the impossibility of conferring theoretical value on a naive ethics based on analogical discourses aimed at supporting, directing and interpreting scientific experience is critically declared.